2016
DOI: 10.1016/j.sysconle.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Transients of platoons with asymmetric and different Laplacians

Abstract: We consider an asymmetric control of platoons of identical vehicles with nearest-neighbor interaction. Recent results show that if the vehicle uses different asymmetries for position and velocity errors, the platoon has a short transient and low overshoots. In this paper we investigate the properties of vehicles with friction. To achieve consensus, an integral part is added to the controller, making the vehicle a third-order system. We show that the parameters can be chosen so that the platoon behaves as a wav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…A good scaling of system norms with such an approach was numerically shown in [10] and the properties of the platoon's response to a step change in leader's velocity were derived in [6]. Using these properties, the parameters of the controller as well as the coefficient of asymmetry can be optimised to minimise the transient time [13]. In both papers [6,13] it was shown that symmetry in position is necessary for a good scaling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A good scaling of system norms with such an approach was numerically shown in [10] and the properties of the platoon's response to a step change in leader's velocity were derived in [6]. Using these properties, the parameters of the controller as well as the coefficient of asymmetry can be optimised to minimise the transient time [13]. In both papers [6,13] it was shown that symmetry in position is necessary for a good scaling.…”
Section: Introductionmentioning
confidence: 99%
“…Using these properties, the parameters of the controller as well as the coefficient of asymmetry can be optimised to minimise the transient time [13]. In both papers [6,13] it was shown that symmetry in position is necessary for a good scaling. In addition, it was proved in [20] that symmetry in position is a necessary condition for "local" string stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Routh-Hurwitz criterion is a standard strategy to derive a concise set of conditions that is equivalent to the condition that all roots of a given polynomial have negative real parts. In various systems similar to the ones discussed here, this criterion gives good results [20,9]. In our current case the resulting equations are too complicated to give us much information and we only get one more necessary condition for stability that we can use, namely Corollary 6.1.…”
Section: Appendix B: the Routh-hurwitz Stability Criteriamentioning
confidence: 87%
“…In doing this one needs to be aware though that (i) assumptions or conjectures needed to solve the old problem must be investigated again as they may not be justified anymore, and (ii) new phenomena may arise. For more details see [20,21,9].…”
Section: Introductionmentioning
confidence: 99%